KEPUTUSAN PETANI TEBU DALAM PENERAPAN SISTEM INTEGRASI TEBU-SAPI POTONG DI KABUPATEN GORONTALO PROVINSI GORONTALO - Sriyani Wahyuni Tangahu; Sri Hartoyo; Anna Fariyanti (Jurnal Bisnis Tani, 2016)
Gorontalo district is one of the areas in the Gorontalo province who get the integrated farming system of sugarcane-beef cattle program. The integrated farming system of sugarcane-beef cattle is one form of technological innovation in agriculture. The purpose of this study is to analyze the factors that influence the farmer’s decision to implement the integrated farming system of sugarcane-beef cattle and to known the factors that provide the greatest opportunities in the implementation of the integrated farming system. This research was conducted with logit analysis, using cross section data obtained from interviews to 59 cane farmers who have cattle. The results showed that the farmer's decision to implement the integrated farming system of sugarcane-beef cattle, significantly influenced positively by a factor of the number of beef cattle, grass garden ownership, extension education, technological mastery of feed and fertilizer. The most factor that give opportunity for farmers to implement the integrated farming system of sugarcane-beef cattle is the number of beef cattle. Thegovernment policy implication, related to the implementation of the integrated farming system of sugarcane-beef cattle that is, the government needs to pay attention to the factors that significantly give positive influence on the implementation of the integrated farming system of sugarcane-beef cattle. Therefore, needed the government policy to increase the number of beef cattle ownership, grass garden ownership, extension education, and technological mastery of feed and fertilizer for sugarcane farmers.